2021
DOI: 10.31083/j.rcm2202058
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit change as a predictor of readmission for decompensated heart failure: a retrospective single centre study

Abstract: In patients with acute heart failure (AHF), hemoconcentration has been suggested as a surrogate for volume changes (AHF). However, literatures comparing the outcome of AHF patients that achieved hemoconcentration during hospitalization with those that do not are limited. The aim of this research is to see if achieving hemoconcentration prior to discharge is linked to a lower risk of re-admission in AHF patients. 124 patients hospitalized in the Cardiology Unit, University Malaya Medical Centre (UMMC) for AHF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Another study in Brazil found that as a predictor of mortality risk in the sepsis, the level of HCT decreased with worse outcomes [ 21 ]. However, a positive relationship between HCT and mortality was found in our study, which was not consistent with some previous studies [ 22 , 23 ]. The differences could be partly explained by two reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study in Brazil found that as a predictor of mortality risk in the sepsis, the level of HCT decreased with worse outcomes [ 21 ]. However, a positive relationship between HCT and mortality was found in our study, which was not consistent with some previous studies [ 22 , 23 ]. The differences could be partly explained by two reasons.…”
Section: Discussioncontrasting
confidence: 99%
“… 26 Studies have shown that optimizing hematocrit levels before discharge contributes to reducing rehospitalization and improving survival in HF patients. 27 , 28 Therefore, we used the optimal cut-off point of hematocrit (35%) to distinguish DiH and DeH as prior studies did. Our analysis revealed that only DiH, but not DeH, was independently associated with short-term outcomes, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory mechanisms to evade tissue hypoxia include an increase in cardiac output by sympathetic stimulation, redistribution of blood flow, an increase in whole-body oxygen extraction ratio, and activation of aortic chemoreceptors with an increase in venomotor tone [ 18 ]. Achievement of hemoconcentration in hospitalized AHF patients showed to have better survival, compared to hemodilution [ 19 ]. Ling et al [ 20 ] showed that plasma volume, which depends on weight and HCT, was a predictor for prognosis in heart failure patients so HCT was also associated with prognosis in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%